Applications of mass spectrometry: certification of a reference material, investigation of plant metabolism and provenance studies - Engin Arı, Betül (My University, 2022)
Mass spectrometry has played a key role in inorganic chemical metrology for more than 25 years. Applications of inductively coupled plasma mass spectrometry (ICPMS) allow wide variety of challenging measurements using different calibration strategies and methodologies with developing technologies. This thesis demonstrates some of the advance applications of ICP-MS in different research areas. In the first chapter, ICP-MS/MS was used in the certification measurements of a candidate seawater reference material. Chemistry Laboratories of TÜBİTAK National Metrology Institute (UME) leaded to process and perform the certification measurements for UME CRM 1206. To be used in certification measurements, isotope dilution mass spectrometry (IDMS) which is a potentially primary technique and triethylamine assisted Mg(OH)2 co-precipitation strategy (TEA/Mg(OH)2) were combined and validated for target analytes. In the second chapter, the investigation of plant metabolization performing total elemental and speciation analyses were conducted by ICP-MS/MS. Vegetables from the Allium genus are of particular importance due to being potential sources of selenium. In this thesis, the metabolization of inorganic selenium fortification of Allium porrum (Leek) at different levels in hydroponic medium was investigated. Growth effect of selenium fortification, uptake and biotransformation rate of inorganic selenium species, translocations, bioavailability and bioaccessibility of selenium were investigated. In the last chapter, pre-investigation for provenance of walnuts were performed by multi element profiling on the walnuts samples and their provenance soils. In the multi element profiling study, walnut samples were analyzed using a high resolution ICP-MS (HR-ICP-MS), while soil analyses were done by using HR-ICPMS and ICP-OES. Optimization of digestion procedures for walnuts and soils were performed and precision, trueness and measurement uncertainties of the proposed methods were evaluated during the method developments. The relationship of elements in walnut and also between walnuts and their soils of origin were evaluated according to the one-to-one correlation coefficient of the elements and the correlation coefficient of different elements pairs.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2022
Keywords: Inductively coupled plasma mass spectrometry; Certification of a reference material; Seawater; Isotope dilution mass spectrometry; Plant metabolization; Selenium; Multi element profiling; Walnut